The Magician's nephew - Lewis, C. S. (Clive Staples), 1898-1963.; Baynes, Pauline; HarperCollins Children's Books (London : HarperCollins Children's Books, 1998)
when Digory and Polly try to return the wicked witch Jadis to her own world, but the magic gets mixed up and they land in Narnia where they witness Aslan blessing the animals with human speech.
Keywords: Narnia (Imaginary place) -- Fiction; Fantastic fiction